Functional state of coronary shunts from the radial artery in the presence of morphological changes in its wall - S. M. Khokhlunov; D. V. Kuznetsov; A. A. Gevorgyan; K. M. Mikhailov; I. F. Nefedova; E. N. Nikolaeva; G. H. Taumova; O. V. Garbuz; M. M. Yokubov (Вестник хирургии имени И.И. Грекова, 2023)
The OBJECTIVE of the research was to study the patency of coronary shunts from the radial artery in the presence of morphological changes in its wall in the period from 40 to 52 months after surgery.METHODS AND MATERIALS. Fragments of 110 radial arteries taken from 103 patients for coronary artery bypass grafting in the period from 2018 to 2021 were subjected to histological examination. To assess the functional state of the shunts in the period from 40 to 52 months after surgery, computed tomography of the coronary arteries (CTCA) with contrast was performed in 66 patients.RESULTS. Histological examination revealed such changes in the radial artery wall as edema of one layer of the artery or all three layers, proliferation of the subendothelial layer of the inner coat, intimal fibrosis, partial obstruction of the artery lumen by a massive accumulation of agglutinated erythrocytes, as well as occlusion of the radial artery. Occlusion of the shunt from the radial artery in the period of 41–42 months was detected in 2 patients who underwent computed tomography of the coronary arteries.CONCLUSION. Statistical analysis of the obtained results revealed that the presence of such morphological changes in the radial artery wall as alteration, exudation and proliferation does not statistically significantly affect the timing of adequate functioning of the shunt.